Estimation of finite population mean in stratified sampling using scrambled responses in the presence of measurement errors. Issue 6 (19th March 2019) - Khalil, Sadia; Gupta, Sat; Hanif, Muhammad
ABSTRACT: This study focuses on the estimation of population mean of a sensitive variable in stratified random sampling based on randomized response technique (RRT) when the observations are contaminated by measurement errors (ME). A generalized estimator of population mean is proposed by using additively scrambled responses for the sensitive variable. The expressions for the bias and mean square error (MSE) of the proposed estimator are derived. The performance of the proposed estimator is evaluated both theoretically and empirically. Results are also applied to a real data set.